A network meta-analysis on the improvement of cognition in patients with vascular dementia by different acupuncture therapies - Wen, Jiayu; Cao, Yu; Chang, Surui; Huang, Qiaoyi; Zhang, Zhen; Wei, Wei; Yao, Jiuxiu; Pei, Hui; Li, Hao (Frontiers in Neuroscience, 2022)
Introduction The second most prevalent cause of dementia is vascular dementia (VaD). Furthermore, acupuncture is a relatively safe and effective traditional therapy. We performed a network meta-analysis to assess the effectiveness and safety of various acupuncture therapies for VaD based on the existing research. Methods To screen for randomized controlled trials (RCTs) comparing different acupuncture treatments in VaD patients, we searched seven electronic databases. The Cochrane tool (Review Manager 5.3) was used to evaluate the risk of bias of the included RCTs. Based on the Grading of Recommendations Assessment, Development and Evaluation framework, we assessed the confidence in the evidence using the Confidence In the results from Network Meta-Analysis approach. We used the frequency approach to perform the network meta-analysis. Data were analyzed using R-4.1.1. Results In total, we included 47 eligible studies. The results of the network analysis showed that the combined interventions of moxibustion (MB) with body acupuncture (BA) (MB + BA) and electroacupuncture (EA) with scalp acupuncture (SA) with BA (EA + SA + BA) were more effective in improving cognitive functions and ability of daily life as compared to SA or BA alone. However, in the subgroup analysis, EA + SA + BA showed better efficacy in short- and mid-term acupuncture as compared with other acupuncture therapies. Conclusion Combined acupuncture therapy may be a safe and effective intervention for individuals with VaD, and MB + BA and EA+SA+BA appear to be the most effective interventions. However, because this study’s analysis was based on low-to-moderate evidence, there remains no strong supporting evidence. High-quality, large-scale, and long-term studies should be conducted in the future to assess the effectiveness and safety of acupuncture in VaD.